GIANT CELL TUMOR OF THE RIBS: A CASE REPORT - I Putu Gede Pradnyadewa Pradana; Mouli Edward (Journal Orthopaedi and Traumatology Surabaya)
Background: Giant Cell Tumor (GCT) is a benign tumor but can be malignant and spread to other organs. Common site of GCT develops in long bone, especially in the knee. A lesion that develops in flat bone is considered rare. This case report aims to recognize GCT of bone and its predilection and help improve diagnostics and manage this case to provide better results.